Strategies for sustainable land management in the East African Highlands - Pender, John; Place, Frank; Ehui, Simeon K. (International Food Policy Research Institute, 2006)
Land degradation is a severe problem in the densely populated highlands of East Africa and elsewhere on the African continent. Soil erosion resulting from cultivation on steeply sloping terrain, mining of soil fertility due to continuous cultivation with limited application of inorganic or organic sources of soil nutrients, and deforestation and overgrazing of rangelands are among the key factors causing low agricultural productivity, widespread poverty, and food insecurity in the region. Finding ways to achieve more sustainable and productive land management is an urgent need, requiring policy, institutional, and technological strategies that are well targeted to the heterogeneous landscapes and diverse bio-physical and socioeconomic contexts found in the East African highlands. This volume helps to address this information need. The book is based on papers originally presented at the conference “Policies for Sustainable Land Management in the East African Highlands,” held at the headquarters of the United Nations Economic Commission for Africa (UNECA) in Addis Ababa in April 2002. That conference was sponsored by the International Food Policy Research Institute (IFPRI); the International Livestock Research Institute (ILRI); the World Agroforestry Centre (formerly ICRAF); the East and Central Africa Program for Agricultural Policy Analysis (ECAPAPA); the African Highlands Initiative (AHI); the Soil, Water and Nutrient Management Program (SWNM) of the CGIAR; the United Nations Economic Commission for Africa (UNECA); and the Regional Land Management Unit (RELMA) of the Swedish International Development Cooperation Agency (Sida). The material focuses on land management issues in Ethiopia, Kenya, and Uganda, which include most of the people and area of the East African highlands.